Organic solvent forward osmosis membranes for pharmaceutical concentration - Goh, Keng Siang (2022)
A scaled-up hollow fibre thin-film composite (TFC) module was successfully developed for organic solvent forward osmosis (OSFO) application in the pharmaceutical industry. The membrane consists of cross-linked P84 polyimide substrate with a polyamide selective layer, formed via interfacial polymerisation. The performance of the lab-scale module was compared to the scaled-up module in reverse osmosis and forward osmosis modes. The results from both tests revealed that the solvent permeability of the scaled-up module decreased while its selectivity increased slightly. This might be caused by the uneven distribution of liquids during interfacial polymerisation, leading to varied membrane performance. The scaled-up module was further tested for OSFO performance using a range of PEG-400 concentrations (0.5–2 M) in acetone and isopropanol as draw solutions. At 2 M PEG-400 concentration, the module demonstrated high isopropanol and acetone permeability of 0.63 LMH and 13.9 LMH, respectively. Moreover, the reverse solute flux of PEG-400 in acetone and isopropanol were relatively low at 0.188 g/l and 0.153 g/l, respectively. The module was further tested for OSFO application in the pharmaceutical industry by concentrating levofloxacin in acetone, using 2 M PEG-400 as draw solution. The process was able to concentrate levofloxacin from 1000 ppm to 16,000 ppm with very low reverse solute flux of 0.178 g/l. Therefore, this work presents a scalable TFC membrane for OSFO application in the pharmaceutical industry.